The human side of productivity Uncovering the role of skills and diversity for firm productivity - Criscuolo, Chiara (OECD Productivity Working Papers, 2021)
Relying on linked employer-employee datasets from 10 countries, this paper documents that the skills and the diversity of the workforce and of managers - the human side of businesses - account on average for about one third of the labour productivity gap between firms at the productivity "frontier" (the top 10% within each detailed industry) and medium performers at the 40-60 percentile of the productivity distribution. The composition of skills, especially the share of high skills, varies the most along the productivity distribution, but low and medium skilled employees make up a substantial share of the workforce even at the frontier. High skills show positive but decreasing productivity returns. Moreover, the skill mix of top firms varies markedly across countries, pointing to the role of different strategies pursued by firms in different policy environments. We also find that managerial skills play a particularly important role, also through complementarities with worker skills. Gender and cultural diversity among managers - and to a lesser extent, among workers - is positively related to firm productivity as well. We discuss public policies that can facilitate the catch-up of firms below the frontier through skills and diversity. These cover a wide range of areas, exerting their influence through three main channels: the supply, upgrading and the matching across firms (the SUM) of skills and other human factors